Effects of Social Distancing and Lockdown Protocols on Fatality Rates of COVID-19 in the U.S. during the First Year of the Pandemic - Valerie Hardoon; Bryant A. Pierce; Solomon C. Mbanefo; Harin N. Shah; Kanav Markan; Marika L. Forsythe (University Library System, University of Pittsburgh, 2023)
Background: SARS-CoV-2, the coronavirus strain responsible for the COVID-19 pandemic, can lead to respiratory diseases ranging in severity. In the early stages, each U.S. state implemented a transition or "phasing" policy that included varying degrees of safety protocols. This allowed the states to slowly reopen while controlling transmission. The initial lockdown was observed to help suppress the pandemic, and our study aimed to determine if there was a correlation between fatality rates and the phase transitions across the states. Methods: Six states from regions with different caseloads were chosen for this study: Florida, California, New York, Washington, Kansas, and Texas. Incidence and mortality rate of COVID-19 were obtained from their respective government websites, allowing case fatality rates to be calculated and compared using Bayesian logistic mixed models. Results: When examining the fatality rates across phases grouped by state, there was a downward trend with each transition except in Texas. However, when the states were combined the overall downward trend was clear, with a median fatality rate of 0.039 in phase 0 dropping to 0.010 by phase 4. Conclusion: Implemented safety protocols and phase transitions were shown to assist in controlling the spread of COVID-19 as the states re-opened. Differences in fatality rates throughout the U.S. can likely be explained by how disciplined each state was with quarantine requirements and social distancing policies. This allowed certain states to control the infectious spread more efficiently than others, thus allowing the states to progress through the phase transitions at different rates.